UNSUR-UNSUR MAGIS DALAM TRADISI PACU JALUR: PERSPEKTIF ANTROPOLOGI AGAMA - Hasbullah Hasbullah; Rendi Ahmad Ashori; Muhammad Nazar al-Masri (Lembaga penelitian dan pengabdian kepada Masyarakat, 2016)
Pacu Jalur tradition is an event that became the pride of the community of Kuantan Singingi. Each year the event was held and the people welcomed enthusiastically. It is marked on the height of the public who attend or watch the course of the race. In addition, winning this race is an honor for the people who have these lines. Spur track involves not only the physical elements, but also things that smells of magic. Shamans become one of the important elements to win the race. Therefore, it is necessary to do in-depth study of the magical element contained in track racing tradition. The study used qualitative methods. Data collection techniques used were observation, interviews, and documentation. Information related to this study was obtained from key informants, namely: shaman path, artisan lane, children runway, track officials, religious leaders, traditional leaders, and community leaders. The results found that magical element present in almost every process in the tradition of spur lines. The persistence of magical elements in this activity because people believe that the power of influence in winning the race